2016
DOI: 10.1007/s10071-016-1010-5
|View full text |Cite
|
Sign up to set email alerts
|

The importance of gestural communication: a study of human–dog communication using incongruent information

Abstract: We assessed how water rescue dogs, which were equally accustomed to respond to gestural and verbal requests, weighted gestural versus verbal information when asked by their owner to perform an action. Dogs were asked to perform four different actions ("sit", "lie down", "stay", "come") providing them with a single source of information (in Phase 1, gestural, and in Phase 2, verbal) or with incongruent information (in Phase 3, gestural and verbal commands referred to two different actions). In Phases 1 and 2, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 15 publications
3
32
1
Order By: Relevance
“…Female dogs also seem to rely more on visual signals than males in their behavioral regulation. A study that aimed to assess the preferred communicative channel between verbal and gestural messages underlined a preference for visual cues in dogs [ 26 ]. A group of Labrador and Golden Retrievers, after acclimatization to four common actions (i.e., sit, down, stay, and come) using bimodal gestural and verbal messages, were subjected to three different conditions.…”
Section: Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female dogs also seem to rely more on visual signals than males in their behavioral regulation. A study that aimed to assess the preferred communicative channel between verbal and gestural messages underlined a preference for visual cues in dogs [ 26 ]. A group of Labrador and Golden Retrievers, after acclimatization to four common actions (i.e., sit, down, stay, and come) using bimodal gestural and verbal messages, were subjected to three different conditions.…”
Section: Perceptionmentioning
confidence: 99%
“…They are responsive to both verbal and non-verbal vocal sounds [ 22 ] and can recognize up to several hundred words [ 23 , 24 ], with specific neural mechanisms that analyze and integrate word meaning and intonation [ 25 ]. They have also evolved an acute sensitivity to human gestures [ 26 , 27 , 28 , 29 , 30 ]. Moreover, it has recently been demonstrated that dogs are able to perceive human emotions via chemosignals, which suggests a type of olfactory communication [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dogs show different sensitivities to conflicting directional gestural cues given concurrently. They tend to follow visual gestural cues more reliably than verbal cues (D'Aniello et al, 2016), and their responses to visual cues are less dependent on signal-giver familiarity (Scandurra et al, 2017). Among the different types of visual directional gestural cues, pointing is more reliably responded to than glancing or gazing (Miklósi et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, dogs have superior hearing to humans and readily form visual associations – even being able to discriminate human facial expressions 2 4 . The experimental literature has shown that dogs can learn associations to almost any stimulus, but demonstrating that certain modalities are innately preferred over others has been difficult 5 . Apart from the basic question of how different sensory modalities impact associative learning in dogs, the answer could affect how dogs are trained in an optimal manner.…”
Section: Introductionmentioning
confidence: 99%